Determination of the relationship between the wrist isokinetic muscle strenght and the grip strength in tennis players aged between 12-14 - Akınoğlu, Bihter (Orthop J Sports Med, 2017)
AIM: The purpose of this study is to determine the relationship between isokinetic wrist muscle strenght and grip strength in tennis players aged between 12-14. METHODS: This study was carried out with the participation of 9 (3 female and 6 male) tennis players aged between 12-14 (means 13,22±0,83). Weight, height, body mass index and dominant extremity of the players were recorded. İsokinetic measurement was performed with Isomed 2000® device. İsokinetic testing protocol; before the test all players performed the wrist flexion and extension isokinetic test with the 5 repeating at 90 º/sec as a warm-up and for comprehenting the test. Then, wrist flexion and extension concentric-concentric strength measurements were performed with the 5 repeating at 60 º/sec and with the 15 repeating at 240 º/sec with the angle between 50 degrees of wrist flexion and 60 degrees of wrist extension and peak torque values were recorded. Standard Jamar® Dynamometer was used for grip strength measurements. Grip strenght was performed firstly in sitting position, which is the position of standard measurement. Secondly, in standing position, the elbow was in full ekstansion and the forearm was in neutral position. Thirdly, in standing position the wrist was positioned approximately 30° extension and 10° ulnar deviation. This test was repeated 3 times in all test position and the mean of three scores were recorded. Firstly, the dominant hand, then the non-dominant hand was evoluated. They were allowed to rest for 30 seconds between each grip measurement. Correlation between peak tork of isokinetic muscle strenght and grip strength was done having been used Spearman correlation test. FINDINGS: It was determined that there was a significant positive relation between wrist flexion-extension isokinetic muscle strength and grip strenght in tennis players aged between 12-14. Clinically, grip strength measured in the standard sitting position was found more as compared to the other positions but these values were not statistically significant (p>0,05). Accordingly, grip strength measured in the standard sitting position correlated with much more of the parameters which we evaluated for isokinetic muscle strength comparing to grip strenght measured in the other two positions (p<0,05). RESULTS: It was concluded that isokinetic muscle strength of wrist can be affected by grip strength, therefore measurement needs to be done in the sitting position which maximum grip strength may reveal.